Analisis Hukum E-Commerce dalam Perspektif Hukum Ekonomi Syariah - Nilam Erman; Haniah Lubis (EL-EMIR Institute, 2026)
The development of e-commerce in the digital era has facilitated trading activities, but has also given rise to various legal issues such as gharar, tadlis, usury, and weak consumer protection. This condition makes the study of e-commerce from the perspective of Sharia Economic Law important to ensure that digital transactions remain in accordance with Sharia principles and provide justice for all parties. This study aims to analyze the validity of e-commerce transactions, identify elements that conflict with Sharia, and explain the application of Sharia Economic Law principles in electronic commerce. The study uses a qualitative approach with library research. Data were obtained from books, scientific journals, academic articles, fatwas of the National Sharia Council (DSN-MUI), and various literature relevant to the research theme. The data analysis technique uses a qualitative descriptive method by outlining and interpreting various concepts of Sharia Economic Law in e-commerce practices. The results of the study indicate that e-commerce transactions are basically permissible in Islam as long as they fulfill the pillars and conditions of the contract and avoid elements of gharar, tadlis, and usury. In addition, the application of the principles of honesty, transparency, and consumer protection is an important aspect in creating a digital trading system that is in accordance with Sharia values.